(untitled) (Malaysian Journal of Civil Engineering, 2023)
The most commonly found steel grades in the market are S 275 and S 355 However, recent advancement in the welding techniques allows for the development of high-strength steel for higher grades up to S 700 with reasonable cost and quality to construct heavy-loaded and long spanned structures. To facilitate the selection of the section sizes in accordance to Eurocode 3 Standard, this research focusses on investigate and validate the bending resistance, Mc,Rd and lateral torsional buckling resistance, Mb,Rd of a hot-rolled steel universal column section (UKC) from common steel grades (S 275 and S 355) up to high strength steels (S 460, S 550 and S 650). This study employed Microsoft Excel spreadsheet to develop a program for design calculation for UKC in accordance with Eurocode 3 Standard and compared with the available results provided in SCI P363. The validated program was further applied to develop selection data for high strength UKC steels (S 460, S 550 and S 650). The study outcome suggests that the classification, Mc,Rd and Mb,Rd of the steel is greatly affected by the steel grade. The parametric study in this research also shows that C1 factor, section size and span length can also affect the Mc,Rd and Mb,Rd of the steel, aside from steel grade. Further analysis of high strength UKC steels was done and tabulated since the program developed was validated and employed in the study